2022
DOI: 10.1136/bmjspcare-2021-003349
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-based supportive therapy on reducing suffering in patients with advanced cancer: randomised controlled trial

Abstract: ObjectivesSuffering is common among patients with advanced cancer. The practice of mindfulness during patient care can potentially reduce suffering. We aimed to examine the efficacy of mindfulness-based supportive therapy (MBST) on reducing suffering in patients with advanced cancer.MethodsWe conducted a parallel-group, single-blinded, randomised controlled trial at the University of Malaya Medical Centre, Malaysia. Seventy-three patients with advanced cancer with an overall suffering score ≥4/10 based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…In the literature, we found 2 studies with opposite results. Tan et al, 19 in a RCT with advanced cancer patients, found statistically significant reduction in the overall suffering score in the MBI group compared with the control group (P = .008). On the contrary, Guan et al, 20 compared MBI to “Normal Listening” (control group) in a PALC setting (n = 60) in Malaysia, and found that, although “Mindful-Breathing” was a quick and easy therapy to administer, the reduction of pain did not reach statistical difference between groups.…”
Section: Discussionmentioning
confidence: 94%
“…In the literature, we found 2 studies with opposite results. Tan et al, 19 in a RCT with advanced cancer patients, found statistically significant reduction in the overall suffering score in the MBI group compared with the control group (P = .008). On the contrary, Guan et al, 20 compared MBI to “Normal Listening” (control group) in a PALC setting (n = 60) in Malaysia, and found that, although “Mindful-Breathing” was a quick and easy therapy to administer, the reduction of pain did not reach statistical difference between groups.…”
Section: Discussionmentioning
confidence: 94%
“…The review identified nine types of death education interventions, including life review intervention ( n = 9), 3846 meaning-centered psychotherapy ( n = 8), 4754 dignity therapy ( n = 7), 5561 Managing Cancer and Living Meaningfully intervention ( n = 7), 6268 combined psychotherapy interventions ( n = 5), 6973 cognitive-behavioral therapy ( n = 3), 74–76 narrative therapy ( n = 3), 77–79 general psychosocial intervention ( n = 3), 80–82 and mindfulness interventions ( n = 2). 83,84 The existing death education intervention pertained to facilitate an understanding of life, and most commonly reported topics included life story ( n = 21), heritage ( n = 16), and life accomplishment ( n = 16). The the understanding of death and adaptation to dying was relatively less covered (Supplemental Appendix 2).…”
Section: Resultsmentioning
confidence: 99%
“…The review identified nine types of death education interventions, including life review intervention (n = 9), [38][39][40][41][42][43][44][45][46] meaning-centered psychotherapy (n = 8), [47][48][49][50][51][52][53][54] dignity therapy (n = 7), [55][56][57][58][59][60][61] Managing Cancer and Living Meaningfully intervention (n = 7), [62][63][64][65][66][67][68] combined psychotherapy interventions (n = 5), [69][70][71][72][73] cognitive-behavioral therapy (n = 3), [74][75][76] narrative therapy (n = 3), [77][78][79] general psychosocial intervention (n = 3), [80][81][82] and mindfulness interventions (n = 2). 83,84 The existing death education intervention pertained to facilitate an understanding ...…”
Section: Research Question 1: Types and Components Of Death Education...mentioning
confidence: 99%
“…Several reasons were identified as to why CBT might be less effective in this patient group. For example, stage IV cancer sufferers undergo more intensive medical treatment, they experience more pain, hospitalisation is more common and ultimately participants are more likely to die during the study (Savard et al, 2006;Serfaty et al, 2020). These factors could potentially lead to lack of engagement with CBT, which could result in increased drop-out rates and poorer outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…There is notably less research available that focuses on psychological interventions for metastatic breast cancer, yet this client group experiences high distress levels and low quality of life (Reed et al, 2012). Studies examining the effectiveness of CBT for depression in people with advanced cancer in general found CBT to be less effective than in people with less advanced cancer (Mustafa et al, 2013;Serfaty et al, 2020). For example, the CanTalk study (Serfaty et al, 2020) provided 12 weeks of 1:1 CBT to people with advanced stage breast cancer and found CBT to be ineffective in treating their depression.…”
Section: Discussionmentioning
confidence: 99%